Short‐term disuse promotes fatty acid infiltration into skeletal muscle - Pagano, Allan F. (J Cachexia Sarcopenia Muscle, 2017)
BACKGROUND: Many physiological and/or pathological conditions lead to muscle deconditioning, a well‐described phenomenon characterized by a loss of strength and muscle power mainly due to the loss of muscle mass. Fatty infiltrations, or intermuscular adipose tissue (IMAT), are currently well‐recognized components of muscle deconditioning. Despite the fact that IMAT is present in healthy human skeletal muscle, its increase and accumulation are linked to muscle dysfunction. Although IMAT development has been largely attributable to inactivity, the precise mechanisms of its establishment are still poorly understood. Because the sedentary lifestyle that accompanies age‐related sarcopenia may favour IMAT development, deciphering the early processes of muscle disuse is of great importance before implementing strategies to limit IMAT deposition. METHODS: In our study, we took advantage of the dry immersion (DI) model of severe muscle inactivity to induce rapid muscle deconditioning during a short period. During the DI, healthy adult men (n = 12; age: 32 ± 5) remained strictly immersed, in a supine position, in a controlled thermo‐neutral water bath. Skeletal muscle biopsies were obtained from the vastus lateralis before and after 3 days of DI. RESULTS: We showed that DI for only 3 days was able to decrease myofiber cross‐sectional areas (−10.6%). Moreover, protein expression levels of two key markers commonly used to assess IMAT, perilipin, and fatty acid binding protein 4, were upregulated. We also observed an increase in the C/EBPα and PPARγ protein expression levels, indicating an increase in late adipogenic processes leading to IMAT development. While many stem cells in the muscle environment can adopt the capacity to differentiate into adipocytes, fibro‐adipogenic progenitors (FAPs) represent the population that appears to play a major role in IMAT development. In our study, we showed an increase in the protein expression of PDGFRα, the specific cell surface marker of FAPs, in response to 3 days of DI. It is well recognized that an unfavourable muscle environment drives FAPs to ectopic adiposity and/or fibrosis. CONCLUSIONS: This study is the first to emphasize that during a short period of severe inactivity, muscle deconditioning is associated with IMAT development. Our study also reveals that FAPs could be the main resident muscle stem cell population implicated in ectopic adiposity development in human skeletal muscle.